Hubungan Antara Pola Asuh Permisif Dengan Perilaku Merokok Siswa Kelas Xi Di Smk Muhammadiyah X - Mega Suci Wulandari; Ghozali Rusyid Affandi (Research Parks Publishing LLC, 2021)
This research aims to determine the relationship between permissive parenting and the behavior of class XI students at SMK Muhammadiyah X. The type of research used was correlational quantitative. The variables used in this study were permissive parenting as the independent variable and smoking behavior as the dependent variable. The population in this study were students of XI grade, 98 students. The sampling technique used was saturated sampling where all the population was sampled. The data collection in this research using a permissive parenting scale and smoking behavior with a Likert scale model. Based on the analysis of the pearson product moment correlation test,it is stated that there is a positive relationship between parenting and smoking behavior with smoking behavior of 0.410 and a significance value of 0.000 <0.005. The coefficient of determination is 0.159 which means that parenting has an effect of 15.9% on the behavior of class XI students at SMK Muhammadiyah X. >